Hometown investment trust funds: An analysis of credit risk - Naoyuki Yoshino; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2014)
In Asia, small and medium-sized enterprises (SMEs) account for a major share of employment and dominate the economy. Asian economies are often characterized as having bank-dominated financial systems and underdeveloped capital markets, in particular venture capital markets. Hence, looking for new methods of financing for SMEs is crucial. Hometown investment trust funds (HIT) are a new form of financial intermediation that has now been adopted as a national strategy in Japan. In this paper, we explain the importance of SMEs in Asia and describe about HITs. We then provide a scheme for the credit rating of SMEs by employing two statistical analysis techniques, principal components analysis and cluster analysis, and applying various financial variables to 1,363 SMEs in Asia. Adoption of this comprehensive and efficient method would enable banks to group SME customers based on financial health, adjust interest rates on loans, and set lending ceilings for each group. Moreover, this method is applicable to HITs around the world.
Keywords: G21; G24; G28; 330; smes; credit risk; hometown investment trust funds; venture capital markets; asian capital markets